STROKE AFTER CORONARY ARTERY BYPASS SURGERY WITH AND WITHOUT CARDIOPULMONARY BYPASS - Iqbal, Javed; Ghaffar, Abdul; Shahbaz, Ahmad; Abid, Abdul Rehman (Journal of Ayub Medical College Abbottabad, 2014)
Background: Stroke is a devastating complication of coronary artery bypass grafting (CABG). This study was carried out with the aim that the development of off pump coronary artery surgery decreases the incidence/adverse outcome due to extra corporeal circulation. Methods: The data utilized in this study was extracted from a randomized controlled trial that was conducted from January 2006 to March 2007 at Punjab Institute of Cardiology. One hundred patients were included in ’˜on pump’ group-A, and 100 patients in ’˜off pump’ group-B. Results: The mean age of the patients in group-A was 53.51±9.96 years and in group-B it was 51.59±10.30 years. Renal failure occurred in 21% patients of group-A as compared to 10% of group-B while Acute Myocardial Infarction occurred in significantly higher number of patients in group-B (11%) as compared to group-A (2%). Off pump was associated with significant decrease in rate of stroke 1.5% as compared to on pump 3.5%. similarly there was decreased in the risk of deaths after stroke 0% as compared to on pump 1.5% mortality after stroke. In group A 6(3.5%) patients developed stroke where as in group-B 2(1.5%) patients developed stroke out of these 6 patients there were 2 mortalities after stroke in group-A while in group-B there was no mortality after stroke within 30 days postoperatively. Conclusion: Off pump CABG is associated with significantly decreased rate of stroke in comparison with the on-pump CABG. Keyword: Coronary artery bypass grafting, Cardiopulmonary bypass, cerebrovascular accident, stroke